2021
DOI: 10.3390/ijerph18189509
|View full text |Cite|
|
Sign up to set email alerts
|

Short-Term Effects of Forest Therapy on Mood States: A Pilot Study

Abstract: Immersion in forest environments was shown to produce beneficial effects to human health, in particular psychophysical relaxation, leading to its growing recognition as a form of integrative medicine. However, limited evidence exists about the statistical significance of the effects and their association with external and environmental variables and personal characteristics. This experimental study aimed to substantiate the very concept of forest therapy by means of the analysis of the significance of its effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 77 publications
2
23
0
Order By: Relevance
“…Similarly, topical use of apiin and hyperoside, after prolonged and repeated exposure to river waters or after their concentration (or extraction from plants) considering the ≤5 µg/L concentration could also work directly on the inflammatory region to improve the symptoms of psoriasis, avoiding adverse systemic effects thanks to the topical administration route [ 34 ]. Overall, the in silico findings described in this work, alongside the importance of protecting from pollution the riverine habitats [ 35 , 36 , 37 , 38 , 39 ] that are particularly rich in forests, living organisms in turn endowed with enormous benefits for human life [ 40 , 41 , 42 , 43 , 44 , 45 ], all concur to highlight the role that pristine rivers have on health and wellbeing of individuals.…”
Section: Resultssupporting
confidence: 54%
“…Similarly, topical use of apiin and hyperoside, after prolonged and repeated exposure to river waters or after their concentration (or extraction from plants) considering the ≤5 µg/L concentration could also work directly on the inflammatory region to improve the symptoms of psoriasis, avoiding adverse systemic effects thanks to the topical administration route [ 34 ]. Overall, the in silico findings described in this work, alongside the importance of protecting from pollution the riverine habitats [ 35 , 36 , 37 , 38 , 39 ] that are particularly rich in forests, living organisms in turn endowed with enormous benefits for human life [ 40 , 41 , 42 , 43 , 44 , 45 ], all concur to highlight the role that pristine rivers have on health and wellbeing of individuals.…”
Section: Resultssupporting
confidence: 54%
“…However, both studies found positive effects on psychological parameters such as stress and anxiety. A recent pilot study from Italy also focuses on psychological effects and confirmed the positive effects on stress and anxiety [109] (level Iia).…”
Section: Forest/forest Therapymentioning
confidence: 75%
“…The aim of this study was to assess whether exposure to inhalable MTs during 3hour-long forest therapy sessions can produce specific effects on anxiety levels. This study follows a previous pilot study, where the total concentration of BVOCs was preliminarily suggested as a contributing factor associated with short-term improvements in mood states, in particular with anxiety reduction of subjects involved in forest therapy sessions organized in remote green areas [14]. To the authors' best knowledge, this is the first attempt, grounded on a large number of participants, to clarify the extent of the effect on anxiety levels of MTs inhaled in a natural setting.…”
Section: Introductionmentioning
confidence: 89%
“…The preventive and healing effects of green environments on psychophysical wellbeing have been documented extensively in the scientific literature, and numerous studies suggest that forest exposure is associated with a wide range of benefits, covering both psychological [1][2][3][4][5], and physiological aspects [6][7][8][9]. In particular, a few experimental studies have demonstrated the effects of forest immersion in stress mitigation and induction of physiological relaxation, especially with regard to anxiety levels [10][11][12][13][14], a topic analyzed in recent literature reviews [5,15,16].…”
Section: Introductionmentioning
confidence: 99%